Inhibitory Tract Traps the Epithelial Na(+) Channel in a Low Activity Conformation - Kashlan, Ossama B. (American Society for Biochemistry and Molecular Biology, 2012)
Proteolysis plays an important role in the maturation and activation of epithelial Na(+) channels (ENaCs). Non-cleaved channels are inactive at high extracellular Na(+) concentrations and fully cleaved channels are constitutively active. Cleavage of the α and γ subunits at multiple sites activates the channel through the release of imbedded inhibitory tracts. Peptides derived from these released tracts are also inhibitory, likely through binding at the inhibitory tract sites. We recently reported a model of the α subunit. We have now cross-linked Cys derivatives of the inhibitory peptide to the channel, using our model to predict sites at a domain interface of the α subunit that is in proximity to the N terminus of the peptide. Furthermore, peptide inhibition was mimicked in the absence of peptide by cross-linking the channel across the domain interface. Our results suggest a dynamic domain interface that can be exploited by inhibitory peptides and provides a mechanism for peptide inhibition and proteolytic activation.